Subcellular Abnormalities of Vestibular Nerve Morphology in Patients With Intractable Meniere's Disease - Wang, Pengjun; Zhu, Huaming; Lu, Wen; Song, Qiang; Chen, Zhengnong; Wu, Yaqin; Wang, Hui; Yu, Dongzhen; Ye, Haibo; Shi, Haibo; Yin, Shankai (Frontiers in Neurology, 2019)
Objective: Few studies so far have focused on the retrocochlear lesions in Meniere's disease (MD). This study aims to investigate pathological alterations in the central portion of the vestibular nerve (VN) in patients with intractable Meniere's disease (MD) and to explore retrocochlear lesions and their relationship with disease severity. Methods: Eight MD patients with refractory vertigo received vestibular neurectomy via a retrosigmoid or translabyrinthine approach. Segments of VN were carefully removed and immediately fixed for histopathological examination. Five VN specimens were examined by light microscopy after hematoxylin/eosin staining; three specimens were extensively analyzed using transmission electron microscopy, to identify VN ultrastructural lesions. Correlations between lesions and patient clinical characteristics were examined. Results: Histopathological examination revealed evidence of various types of chronic VN impairment, including the formation of corpora amylacea (CA), axon atrophy, and severe damage to the myelin sheath. Electron microscopy revealed membranous whorls within dilated Schmidt–Lanterman incisures, the formation of myeloid bodies, dysmyelination, and demyelination. Unexpectedly, we observed a positive correlation between the density of CA in VN tissue and the duration of disease, as well as the degree of hearing impairment, independent of age. Conclusion: Our findings indicate that deformation of subcellular organelles in the central portion of the VN is one of the key pathological indicators for the progressive severity and intractability of vertigo and support a vestibular nerve degeneration.